A Large Anterior Urethral Calculus Presenting as Urethrocutaneous Fistula - Biswanu Sundar Biswal; Vikalap Gupta; Suren Kumar Das; Debabrata Kumar Sabat (مجله كليه طب الكندي, 2023)
Presentation of urinary calculus ranges from painful urination to acute retention. Diagnosed by x-ray pelvis and non-contrast CT and removal of stone by various methods is the management. Variety in symptoms, sometimes make clinical diagnosis difficult until radiological investigations confirm it. In this case presentation, initial diagnosis was made of Urethrocutaneous fistula may be due to distal stricture, but on investigating, he was diagnosed as urethral calculus in urethral diverticulum , as the reason for his symptoms